Las medidas para contrarrestar la crisis de la eurozona y su impacto en el modelo social europeo - Pinelli, Cesare (Revista de Derecho, 2019)
The Author seeks to demonstrate that the impact of the eurozone’s financial crisis on the European social model is due both to scarce capacity of the EU political institutions in managing that crisis and to the fact that, in the last decade, the launch of the European social model was not accompanied with the political conditions aimed at meeting the challenges posed from a powerful non-regulated global financial market. To this end, after having exposed the main features of the EU economic governance, the author draws attention on the instruments (Six pack, Fiscal Compact, ESM) recently adopted from the EU or its single member States with the aim of reacting to the financial crisis. According to the Author, the failures of these instruments depend on the national governments’ anawareness of the risks posed from the current crisis for the whole construction of the EU.